(untitled) (Research, Society and Development, 2020)
The skin has the ability to be a physical barrier against the entry of microorganisms into the body. The trauma caused by burns disrupts this function, which facilitates the invasion of external pathogens. Sepsis is a serious implication that can occur in burn patients. The aim of this study is to address the cause of sepsis, the main pathogens involved in development and its severity in burn patients. Methods: This is an integrative literature review of complete articles available on SciELO, Medline and Lilacs platforms using the descriptors: "Burns" and "Sepsis". After the analytical reading, only 05 articles met the inclusion criteria and were used to compose the final sample of this study. In the descriptive analysis, it was possible to summarize and evaluate the data from the selected articles. Articles that were framed as research on human beings with publication year between 2015 and 2020 were used. Results: Sepsis is the main cause of mortality in patients with severe burns, which can lead the patient to septic shock. The diagnosis is difficult the faster it occurs the greater the chances of successful treatment. The main pathogens that lead to sepsis in burns are Staphylococcus aureus, Acinetobacter sp, Candida albicans and Proteus sp. Conclusions: Pathogens act differently in each person, depending on factors such as age, pre-existing diseases, immunity, among others. Proper patient management is essential for a good prognosis and must be done by a multiprofessional team in order to address the patient’s diverse needs.